TAX AMNESTY - Suyanto Suyanto; Pasca Putri Lopian Ayu Intansari; Supeni Endahjati (Jurnal Akuntansi, 2016)
This study aims to determine the taxpayer's perception about the Tax Amnesty to compliance of the individual taxpayer. The nature of this research is a descriptive study with a quantitative approach. The method of analysis in this research is to use simple regression. Questionnaires are processed a total of 41 questionnaires. Results from this study is the perception Taxpayer positive effect on tax compliance. Based on test results, the obtained value of t arithmetic amounted to 3.244 higher than the t value is 1.6829 with a significance value of 0.002, thus Ha supported. Keyword: Tax Amnesty Program, Taxpayer’s Complience.